Anti-estrogen Treatment in Endometrial Cancer: A Systematic Review - van Weelden, Willem Jan; Massuger, Leon F. A. G.; , ENITEC; Pijnenborg, Johanna M. A.; Romano, Andrea (Frontiers in Oncology, 2019)
Introduction: Hormonal therapy in endometrial cancer (EC) is used for patients who wish to preserve fertility and for patients with advanced or recurrent disease in a palliative setting. First line hormonal therapy consists of treatment with progestins, which has a response rate of 25% in an unselected population. Treatment with anti-estrogens is an alternative hormonal therapy option, but there is limited data on the effect and side-effects of anti-estrogens in EC. Therefore, we performed a systematic review to investigate the response rate and toxicity of anti-estrogenic therapy in patients with endometrial cancer. Methods: A systematic search in electronic databases was performed to identify studies on selective estrogen receptor modulators (SERM) and down-regulators (SERD) and aromatase inhibitors that reported on response rates among EC patients. Outcome in estrogen receptor (ER) positive and negative disease was assessed independently. Results: Sixteen studies on advanced stage and recurrent EC were included. Ten studies investigated anti-estrogen monotherapy and seven investigated a combination of anti-estrogenic drugs with either progestin or targeted treatment. Due to heterogeneity in patient population, no meta-analysis was performed. The median age of the patients in the included studies ranged from 61-71 years and the proportion of low grade tumors ranged from 38-80%. The RR for tamoxifen ranged from 10-53%, for other SERMs and SERDs 9-31%, for aromatase inhibitors from 8-9%, for combined tamoxifen/progestin treatment 19-58%, for combined chemo- and hormonal therapy 43% and for combination of anti-estrogenic treatment with mammalian target of rapamycin (mTOR) inhibitors 14-31%. Toxicity consisted mainly of nausea and thrombotic events and was higher in combination therapy of chemotherapy and hormonal therapy and hormonal therapy and mTOR inhibitors compared to other therapies. Conclusion: Tamoxifen or a combination of tamoxifen and progestin should be the preferred choice when selecting second line hormonal treatment because the RRs are similar to first line progestin treatment and the toxicity is low. The response can be optimized by selecting patients with endometrioid tumors and positive estrogen receptor status, which should be based on a pretreatment biopsy.